Auto-immune anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis: three case reports. (3rd July 2017) - Bashiri, Fahad A.; Al-Rasheed, Abdulrahman A.; Hassan, Saeed M.; Hamad, Muddathir H. A.; El Khashab, Heba Y.; Kentab, Amal Y.; AlBadr, Fahad B.; Salih, Mustafa A.
Abstract : Anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis is a recently identified auto-immune disorder characterised by severe memory deficit, a decreased level of consciousness, seizures, autonomic dysfunction and movement disorders. Three girls with the disorder are reported; they were aged 4 years, 5 years and 10 months. The 10-month-old infant who is one of the youngest patients reported with anti-NMDAR encephalitis worldwide, had MRI features suggestive of herpes simplex encephalitis (known to trigger anti-NMDAR encephalitis), but CSF PCR for herpes simplex was negative. All the patients presented with seizures, behavioural change, regression of speech, dystonia and choreo-athetosis. Anti-NMDAR antibodies were detected in all patients' sera and cerebrospinal fluid (CSF). Intravenous immunoglobulin, corticosteroids and rituximab were administered at different intervals. Cases 1 and 2 made a full recovery, but case 3 has mild motor and speech delay. Patients who present with encephalopathy, seizures and movement disorders should be tested for anti-NMDAR antibodies in serum and CSF in addition to being screened for herpes simplex encephalitis.